Malaysian growth centiles for children under six years old - Bong, Y.; Shariff, A.A.; Mohamed, A.M.; Merican, A.F. (Informa Healthcare, 2015)
Background: Growth references are useful for the screening, assessment and monitoring of individual children as well as for evaluating various growth promoting interventions that could possibly affect a child in early life. Aim: To determine the growth centiles of Malaysian children and to establish contemporary cross-sectional growth reference charts for height and weight from birth to 6 years of age based on a representative sample of children from Malaysia. Methods: Gender-and age-specific centile curves for height and weight were derived using the Cole's LMS method. Data for this study were retrieved from Malaysian government health clinics using a two-stage stratified random sampling technique. Assessment of nutritional status was done with the SD scores (Z-scores) of WHO 2006 standards. Results: Boys were found to be taller and heavier than girls in this study. The median length of Malaysian children was higher than the WHO 2006 standards and CDC 2000 reference. The overall prevalence of stunting and underweight were 8.3% and 9.3%, respectively. Conclusions: This study presents the first large-scale initiative for local reference charts. The growth reference would enable the growth assessment of a Malaysian child compared to the average growth of children in the country. It is suggested that the use of WHO 2006 Child Growth Standards should be complemented with local reference charts for a more wholesome growth assessment.